Cystic fibrosis presenting as small bowel obstruction in pediatric patient: a case report - Devi, Pinki; Nisha Marwah; Swarnim Dalakoti; Vibhuti Thukral; Jyoti Dahiya; Sunita Singh (International Journal of Research in Medical Sciences, 2023)
Intestinal obstruction complete or incomplete has been found commonly in patients with cystic fibrosis in all age groups with variable presentation. Prevalence of intestinal obstruction in children with cystic fibrosis is 7-8%. Neonates present with meconium ileus due to inspissated meconium and complete obstruction. This case demonstrates similar presentation in a pediatric patient. A six day old male patient presented in the pediatric surgery department with abdominal distention, vomiting and fever. Patient was operated and intraoperative meconium plug was seen along with dilated proximal bowel, filled with sticky meconium. Resected gut segment was received in the Department of Pathology. Grossly dilated gut segment on cut section was seen filled with thick putty like greenish fecal matter. Histopathological examination showed features consistent with cystic fibrosis. There are multiple causes for intestinal obstruction in neonates, cystic fibrosis can be one of them which needs to be considered by the clinicians. Such cases need to be reported for better understanding of their clinico-pathological presentation and prevalence.